2006
DOI: 10.1088/0031-9155/51/19/016
|View full text |Cite
|
Sign up to set email alerts
|

Method comparison of ultrasound and kilovoltage x-ray fiducial marker imaging for prostate radiotherapy targeting

Abstract: Several measurement techniques have been developed to address the capability for target volume reduction via target localization in image-guided radiotherapy; among these have been ultrasound (US) and fiducial marker (FM) software-assisted localization. In order to assess interchangeability between methods, US and FM localization were compared using established techniques for determination of agreement between measurement methods when a 'gold-standard' comparator does not exist, after performing both technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…They concluded that concordance of resulting TAUS prostate and SC FM measurements was "poor" or "unacceptable" with 95% of measures within 15 mm. 61 Numerous other groups have found significant differences in treatment setup data derived from TAUS soft-tissue assessment compared with FM data from other modalities, greater variation within ultrasound data and ultrasoundderived PTV margins may be up to 3-4 times smaller than those reported in the literature. 43,62,63 Fuller et al 61 also provide a useful narrative on the inherent difficulties of comparing IGRT modalities which briefly include the lack of an established ground truth and the statistical inaccuracies of comparing data generated by incomparable methods or devices.…”
Section: Imaging Modalitiesmentioning
confidence: 86%
See 1 more Smart Citation
“…They concluded that concordance of resulting TAUS prostate and SC FM measurements was "poor" or "unacceptable" with 95% of measures within 15 mm. 61 Numerous other groups have found significant differences in treatment setup data derived from TAUS soft-tissue assessment compared with FM data from other modalities, greater variation within ultrasound data and ultrasoundderived PTV margins may be up to 3-4 times smaller than those reported in the literature. 43,62,63 Fuller et al 61 also provide a useful narrative on the inherent difficulties of comparing IGRT modalities which briefly include the lack of an established ground truth and the statistical inaccuracies of comparing data generated by incomparable methods or devices.…”
Section: Imaging Modalitiesmentioning
confidence: 86%
“…Using the ExacTrac® 6D IGRT system (Brainlab AG, Feldkirchen, Germany), Shi et al 60 In a series of 40 patients, Fuller et al 61 compared treatment setup errors derived from in-room TAUS imaging of the prostate with those from kV SC images of prostate FMs for radiotherapy verification. As in Barney et al, the purpose of this comparison study was not to establish which modality was superior, although treatment was corrected and treated according to SC FM position.…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…They reported that the technique was useful in 95.8% of setups, a significant improvement from traditional ultrasound methodologies. Despite these advances, ultrasound imaging remains challenging in the vast majority of tumor sites, and the use of stereotactic ultrasound is now largely restricted to applications in prostate cancer (Chinnaiyan et al 2003;Fuller et al 2006;Peignaux et al 2006). …”
Section: Stereophotogrammetric Methods Of Stereotactic Localizationmentioning
confidence: 99%
“…It is used in patient respiration phase monitoring to command a 4 dof robot, and is tested in proton therapy for brain tumour at Massachusetts General Hospital. For prostate radiotherapy targeting, a comparative study between ultrasound and x-ray imaging of markers is proposed in [7].…”
Section: Introductionmentioning
confidence: 99%